Fashion design (apparel) advanced (3G Elearning FZ LLC, 2016)
"Fashion Design (Apparel): Advanced combines many different practical and visual skills with knowledge of specialized materials and techniques. Fashion design is a form of art dedicated to the creation of clothing and other lifestyle accessories. Fashion design is influenced by cultural and social attitudes, and has varied over time and place. This book will introduce the knowledge and skills for those studying and/or working in garment industry"--Provided by publisher.